The ESCRT-III complex is required for nuclear pore complex sequestration and regulates gamete replicative lifespan in budding yeast meiosis. Issue 1 (1st January 2020) - Koch, Bailey A.; Staley, Elizabeth; Jin, Hui; Yu, Hong-Guo
ABSTRACT: Cellular aging occurs as a cell loses its ability to maintain homeostasis. Aging cells eliminate damaged cellular compartments and other senescence factors via self-renewal. The mechanism that regulates cellular rejuvenation remains to be further elucidated. Using budding yeast gametogenesis as a model, we show here that the endosomal sorting complex required for transport (ESCRT) III regulates nuclear envelope organization. During gametogenesis, the nuclear pore complex (NPC) and other senescence factors are sequestered away from the prospore nuclei. We show that the LEM-domain protein Heh1 (Src1) facilitates the nuclear recruitment of ESCRT-III, which is required for meiotic NPC sequestration and nuclear envelope remodeling. Furthermore, ESCRT-III-mediated nuclear reorganization appears to be critical for gamete rejuvenation, as hindering this process curtails either directly or indirectly the replicative lifespan in gametes. Our findings demonstrate the importance of ESCRT-III in nuclear envelope remodeling and its potential role in eliminating senescence factors during gametogenesis.